Fermions Tunneling and Quantum Corrections for Quintessential Kerr-Newman-AdS Black Hole - Wajiha Javed; Rimsha Babar (Advances in High Energy Physics)
This paper is devoted to study charged fermion particles tunneling through the horizon of Kerr-Newman-AdS black hole surrounded by quintessence by using Hamilton-Jacobi ansatz. In our analysis, we investigate Hawking temperature as well as quantum corrected Hawking temperature on account of generalized uncertainty principle. Moreover, we discuss the effects of correction parameter β on the corrected Hawking temperature Te-H, graphically. We conclude that the temperature Te-H vanishes when β=100, whereas for β<100 and β>100, the temperature turns out to be positive and negative, respectively. We observe that the graphs of Te-H w.r.t. quintessence parameter α exhibit behavior only for the particular ranges, i.e., 0<α<1/6, charge 0<Q≤1, and rotation parameter 0<a≤1. For smaller and larger values of negative Λ, as horizon increases, the temperature decreases and increases, respectively.